THE IMPLEMENTATION OF SCANNING TECHNIQUE IN IMPROVING READING COMPREHENSION AND MOTIVATION OF GRADE VIII STUDENTS AT MTs MUHAMMADIYAH NUNU - Hijrah, Hijrah (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
This research is to measure the effect of the implementation of scannning technique. This quasi-experimental research took 18 students of grade VIIIA for the experimental class and 16 students of grade VIIIB for the control on the sample. They were chosen purposively. The instruments of data collection were an essay reading test and the questionnaire items to measure the students’ motivation toward the scanning technique. The data of the research uses independent t-test formula by applying degree of freedom (df) = 32 (18+16-2) with the level of significance 0.05. The results of data analysis indicate that the students’ mean score of the posttest is79 in experimental class is higher than the mean score of the control class 60. It proves that there is a significant difference of students’ reading comprehension that are taught by scanning technique and those who are not taught by scanning technique. Furthermore, the data analysis by applying independent t-test shows that the value of tcounted 6.44 is higher than ttable 2.037. It explains that the implementation of scanning technique has impact on the students’ reading comprehension. The last result which has been also analyzed that the mean score of students’ motivation who are taught scanning technique 73 is higher than those who are not taught the scanning technique 68. The analysis of questionnaire data also indicates that the value of tcounted 2.33 is higher than ttable 2.037. It means that there is a significant difference of the students’ motivation that are taught by scanning technique and those who are not taught by scanning technique. Both of the test and questionnaire analysis prove that Ha of the research is accepted and Ho is rejected. In other words, the implementation of scanning technique can improve students’ reading comprehension and motivation.